Role of Green Chemistry in Ecosystem Restoration to Achieve Environmental Sustainability - Srivastav A.L.; Grewal A.S.; Markandeya; Pham T.D. (My University, 2025)
Role of Green Chemistry in Ecosystem Restoration to Achieve Environmental Sustainability deals with current challenges of environmental problems along with the approaches of environmental sustainability in alliance with green chemistry. The book shows how to lessen the impact on the environment by maintaining a balance between society, the environment, and the economy, all of which are regarded as fundamental pillars of sustainability. Furthermore, policymakers and scholars will gain insights into how to develop and explore innovative techniques for achieving sustainable development goals. This book is unique in the field of environmental sustainability, as it is based on green chemistry concepts. © 2024 Elsevier Inc. All rights reserved, including those for text and data mining, AI training, and similar technologies.